Exploring the potential mechanism of Dayuanyin in treating acute lung injury: A network pharmacology and experimental verification approach - Huang, Bei; Zhang, Wen; Li, Rui; Xie, Yifei; Yang, Haiguang; Song, Junke; Pang, Xiaobin; Du, Guanhua (Pharmacological research. Modern Chinese medicine, 2024)
Dayuan Yin (DYY) is a classical formula used for treating plague, known for anti-inflammatory and antioxidant effects. It has shown potential in alleviating acute lung injury (ALI), though its mechanisms remain unclear. This study aimed to investigate the effects and mechanisms of DYY in treating ALI. Network pharmacology and molecular docking techniques were used to elucidate the potential targets and mechanisms of DYY in treating ALI. Subsequently, in vivo experiment was performed to verify the findings from bioinformatics analysis. λ-Carrageenan (λ-Car) was used to establish the ALI model. At 1 h before 2% λ-Car injection, 3 g/kg or 9 g/kg DYY were administered orally. 4 h after λ-Car-induced injury, the efficacy of DYY in treating ALI was assessed using several methods, including Wright-Giemsa staining to examine inflammatory cells in mouse pleural exudates, hematoxylin and eosin staining of lung tissues, and serum cytokine levels, cytokine mRNA levels in lung tissues, key protein levels were detected. Network pharmacology and molecular docking analyses suggested that signal transducer and activator of transcription 3 (STAT3), interleukin-6, and tumor necrosis factor alpha might be the key regulated proteins, while the nuclear factor kappa-B (NF-κB) pathway could be the pathway involved. In vivo, the lung injury score of mice decreased to 0.78 from 3.44 after treating 9 g/kg DYY. Compared with the λ-Car group, the number of inflammatory cells in the DYY groups were decreased by 63 - 73% in pleural effusion. Further analysis showed that DYY could reduce the release of inflammatory cytokines, inhibit the activation of NF-κB signaling pathway, and downregulate the expression of p-janus kinase 2 (JAK2), p-STAT3, and matrix metalloproteinase-9 (MMP-9), thereby protecting against ALI. The study revealed remarkable potential of DYY in alleviating λ-Car-induced ALI through inhibiting the JAK2/STAT3/MMP-9 and NF-κB signaling pathways. [Display omitted]